PERANCANGAN DAN PEMBUATAN STREAMING RADIO ONLINE BERBASIS ANDROID MOBILE - Effendy, Dedi Usman; Mukhsim, M. (DINAMIKA DOTCOM, 2014)
Internet radio is also known as web radio , net radio, streaming radio or e - radio is an audio broadcasting service transmitted via the Internet . Broadcasting is done via the internet referred to as webcasting since it is not transmitted broadly through wireless means . Internet radio have a streaming media that can provide a continuous audio channels and no operational control of broadcasting such as traditional broadcast media in general .The means used to broadcast Internet radio is via streaming technology , a technology that can receive and send information from one party to another party to use tool that can receive streaming media streams as well. The streaming technology using a lossy audiocodec , which is a computer program that serves to compress audio and video data is formatted based on the sound streaming through the radio to the internet .Setting Server Testing , Testing Setting SDK and AVD Manager , Main Project , Tests on PC Emulator, Test Build. Apk Android Mobile Application Testing to the Install on Mobile and to perform initial settings on streaming online radio certainly already installed SDK and AVD in Eclipse, Class start Streaming Audio ( ) is used to run and control the progressbar and Radio Server URL is used.Keywords: Streaming, Radio online, Android mobile, Java, MySQL